Potensi Pembelajaran STEAM dalam Konsep Pengukuran di SMA di Kabupaten Jepara - Putri, Belinda Chintya Rosady; Indianti, Intan; Patonah, Siti (Universitas PGRI Semarang, 2024)
The following research aims to analyze the usage of STEAM approach in learning measurements. This research is qualitative type research. Physics class in senior high school tends to be strictly theoretical with no practical with minimal usage of things that could be found nearby as a learning object. The researcher aims to describe the potential of using the STEAM approach in learning measurements done by senior high school physics teachers in Jepara. The preferred method of data collection of this research are observation, interview and questionnaires about implementing the STEAM approach in learning measurements concept. The results show 97% of the teachers are aware of the STEAM approach. 62% of teachers have implemented the STEAM approach in learning measurements and 52% of the teachers that have implemented STEAM approach state that the approach is effective in tackling learning obstacles in student.